TEACHING LEXICALLY FROM VERTICAL LISTS TO HORIZONTAL ALTERNATIVES - Dedy Subandowo (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2015)
Abstract Teaching vocabulary for young learners by giving it into semantic set will not help them understand how the words are used. In elementary coursebook, the vocabulary is presented in list semantic set that is semantically related items such as jobs doctor, teacher, lawyer etc. or colours: red, blue, yellow etc.). This idea is really restrictive to develop the students’ vocabulary mastery. It seems that teaching vocabulary in semantically related items is counter-productive but this idea has never been taken on board. The question is Why do students have to go through so much learning of things which they are hardly ever likely to say?. (Estatiev, 2015) and (Leoselivan, 2014) introduce the way to teach students’ vocabulary by developing the students’ idea through communicative purpose beyond the basic description. Developing alternatives in horizontal lists instead of semantic set lists will make learners find the words in which they are likely to go with (co-text) rather than with other words sharing the same superordinate concept. The easy samples are colour and animal. Focusing them in three at a time and present would be more affective to fix the word collocation such as noun that can go along with adjective or noun collocation. Keyword: EFL, Semantic Set, Teaching Lexically, Vocabulary Mastery